Solar drying adds value to surplus fruit and vegetables - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In Burkina Faso production from market gardening has tripled in less than ten years, mainly because water resources are being better used. This has meant that at harvest time local markets are now frequently over-supplied. As a result prices plummet...